Nipah Encephalitis – A Dangerous Zooanthroponosis Of Indo-Malaysian Region Of South-Еast Asia - E. P. Lukin (Журнал инфектологии, 2014)
The review provides information on a new zooanthroponosis – Nipah encephalitis. Characteristics of the pathogen and its ecology and clinic are presented. The purpose of the review is to get Russian specialist acquainted with new dangerous disease unknown in Russia. The research method – analytical. Infection by humans were first described in Malaysia (1999), after in Bangladesh (2004) and India (2006). The causative agent was identified as a new member of paramyxoviruses and then, together with related Hendra virus, separated in a new genus Henipavirus of the family Paramyxoviridae (2000). Reservoir in nature – fruit bats, predominantly carnivorous flying foxes of 8 species of the genus Pteropus, secondary reservoir – domestic pigs. Nipah virus is highly contagious for humans and swine. The last act as amplifying and reservoir host. The disease inhumans is characterized by symptoms and signs of acute encephalitis and pulmonary insufficiency. Rapidly developing coma, lethality – up to 92,0%. Outbreaks with transmission of the virus from person-to-person are known. Specific treatment has not been developed, prevention is nonspecific.